ASSESSING THE PERFORMANCE OF POLICE CIVIL SERVANTS (SATPOL PP) OFFICERS IN ENFORCEMENT OF PUBLIC ORDER: EMPIRICAL STUDY OF DISCIPLINE AND ETHICS - Gugi Gustamam; Rizki Tri Anugrah Bhakti; Rabu; Dwi Afni Maileni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the performance of Satpol PP officers in enforcing public order, with a particular focus on work discipline and ethical behavior as fundamental aspects of public service accountability. Despite a clear legal mandate given to Satpol PP, challenges remain in ensuring that law enforcement practices are carried out in accordance with ethical standards and professional norms. This study aims to analyze how the legal framework and organizational factors influence the actual implementation of public order enforcement by Satpol PP officers. This study uses a normative-juridical approach combined with empirical qualitative methods. The normative analysis was conducted by examining laws and regulations, codes of ethics, and standard operating procedures that govern the authority and duties of Satpol PP. Empirical data were collected through in-depth interviews, field observations, and document analysis involving Satpol PP officers and relevant stakeholders at the local government level. The collected data were analyzed using thematic analysis to identify patterns and discrepancies between legal norms and field practices. The findings indicate that the gap between normative regulations and empirical implementation is influenced by factors such as leadership practices, organizational culture, legal understanding, and internal oversight mechanisms. These factors significantly influence the consistency of discipline and ethical behavior in enforcing public order. This study makes a practical contribution by offering recommendations for strengthening legal compliance, ethical governance, and performance evaluation mechanisms within the Public Order Agency (Satpol PP). Theoretically, this research enriches empirical legal studies by integrating normative analysis with field-based evidence in the context of public order enforcement.